Adopting E-commerce Technology for SME’s (Case study in Tangerang, Indonesia) - Nadia Nadia; Evawaty Tanuar; Agnes Kurniati T (Bina Nusantara University, 2019)
E-commerce is one of the trend technology to help a business. It can help business for the marketing, simplyfy and facilitate business steps, reach out the diﬀerent and much more potential customers. Though there are so many beneft of e-commerce, are the Small Medium Enterprise, especially Micro Enterprise able to take that opportunities? To distribute and introduce E-commerce adn it’s advantage, workshop and mentoring conducted for 31 Micro enterprise was held in Tangerang. The participant learning about e-commerce and try to implement their business using that. Participant able to adapt to e-commerce and also compare get knowladge for diﬀerent type of e-commerce on their understanding. In the usability testing, shows that the participant able to use the application and doing transaction. While the impact on the business itself still need to be explore more in future.